Necrotizing enterocolitis in a term newborn after spontaneous cerebral parenchymal hemorrhage: a case report - Lijuan Zhang; Weifeng Lu (BMC, 2024)
Abstract Background Necrotizing enterocolitis (NEC) and intracranial hemorrhage are severe emergencies in the neonatal period. The two do not appear to be correlated. However, our report suggests that parenchymal brain hemorrhage in full-term newborns may put patients at risk for NEC by altering intestinal function through the brain-gut axis. Case presentation We present a case of spontaneous parenchymal cerebral hemorrhage in a full-term newborn who developed early-stage NEC on Day 15. Conclusions It is possible to consider brain parenchymal hemorrhage as a risk factor for the appearance of NEC. Clinicians should be highly cautious about NEC in infants who have experienced parenchymal hemorrhage. This article is the first to discuss the relationship between parenchymal hemorrhage and NEC in full-term newborns.